2007
DOI: 10.1007/s12020-007-9005-2
|View full text |Cite
|
Sign up to set email alerts
|

A selective androgen receptor modulator with minimal prostate hypertrophic activity enhances lean body mass in male rats and stimulates sexual behavior in female rats

Abstract: Androgen receptor (AR) ligands with tissue selectivity (selective androgen receptor modulators, or SARMs) have potential for treating muscle wasting, hypogonadism of aging, osteoporosis, female sexual dysfunction, and other indications. JNJ-28330835 is a nonsteroidal AR ligand with mixed agonist and antagonist activity in androgen-responsive cell-based assays. It is an orally active SARM with muscle selectivity in orchidectomized rat models. It stimulated growth of the levator ani muscle, stimulating maximal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…Estrogen was administered to elicit sexual behavior; however progesterone is required to facilitate both proceptive and receptive behaviors (Erskine, 1989). Allan et al (2007) were the first to report the effectiveness of SARMs in female rats, showing that a pyrazoline-derived SARM was able to enhance a female's preference for sexually active males.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen was administered to elicit sexual behavior; however progesterone is required to facilitate both proceptive and receptive behaviors (Erskine, 1989). Allan et al (2007) were the first to report the effectiveness of SARMs in female rats, showing that a pyrazoline-derived SARM was able to enhance a female's preference for sexually active males.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators did not report assays in intact rats, so it is not clear how common is this property of JNJ-37654032. We have also observed mixed prostate agonism and antagonism with a series of pyrazoline SARMs [23,32].…”
Section: Discussionmentioning
confidence: 70%
“…5A and data not shown). Likewise, DHT increased fat mass in a separate study [32]. In contrast, TP and orchidectomy alone had no effect on fat mass.…”
Section: Discussionmentioning
confidence: 74%
“…Several groups recently discovered a structurally distinct class of orally active nonsteroidal compounds that exert weaker effects on the prostate while maintaining anabolic effects in muscle and the bone (Allan et al, 2007;Miner et al, 2007;Vajda et al, 2009). In the present study, we first observed that TSAA-291, a steroidal antiandrogen previously used to treat benign prostatic hyperplasia used in Japan, displayed partial agonist activity in reporter assays using COS-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…SARM is defined as compounds that specifically bind to the androgen receptor and exert agonistic/antagonistic effects in a tissue-specific manner (Negro-Vilar, 1999). SARM displaying tissue-selective anabolic effects in muscle and the bone without exerting adverse effects on prostate or latent prostate cancer would be a useful therapeutic option for sarcopenia, osteoporosis, muscle wasting associated with cancer cachexia, and aging-associated functional limitations (Allan et al, 2007;Miner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%